Distal Impact Ejecta Layers A Record of Large Impacts in Sedimentary Deposits - Glass, Billy P.; Simonson, Bruce M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Impact cratering is an important geological process on all solid planetary bodies, and, in the case of Earth, may have had major climatic and biological effects. Most terrestrial impact craters have been erased or modified beyond recognition. However, major impacts throw ejecta over large areas of the Earth's surface. Recognition of these impact ejecta layers can help fill in the gaps in the terrestrial cratering record and at the same time provide direct correlation between major impacts and other geological events, such as climatic changes and mass extinctions. This book provides the first summary of known distal impact ejecta layers
Impact Crater Formation -- Distal Impact Ejecta Layers -- Modeling Variations in Distal Impact -- Distal Impact Ejecta Layers and Earth History.
Keywords: Geography; Geology; Physical geography; Sedimentology; Planetology; Earth Sciences; Geology; Geophysics/Geodesy.; Planetology; Sedimentology